Classroom goal structure in the learning of mathematics - Yaakub, Noran Fauziah; Awang Hashim, Rosna (Universiti Pendidikan Sultan Idris, 2004)
According to achievement goal theory, classroom learning environment or contextual factors influence students' learning. For instance, classroom that promotes mastery learning may cultivate or inculcate task-focused goals among students. However, classroom that focuses too much on competition may encourage performance goal.Studies on classroom goal structure have focused on the relationship between the purpose or meaning of achievement behaviour that is communicated to (by teachers) and perceived (by students) and a variety of student beliefs and behaviours. The objective of this paper is to examine students' perception of classroom goal structure or orientation as communicated by their teachers. This study on 1849 adolescents (900 males and 949 females) from 30 secondary schools in the northern state of the country found them to be more task-focused (promoting mastery learning) than performance focused. There were differences in the two dimensions of classroom goal structure in terms of some selected independent variables. The findings of the study bear some implications for theory and practice.